Study on Influence of Joint Distribution on Surrounding Rock Failure of an Underground Tunnel. (12th October 2021) - Liu, Wanrong; Peng, Chao; Zhang, Baoliang
Abstract : Due to geological structure and artificial disturbance, a large number of joints and fissures are formed in the surrounding rock of an underground tunnel. In order to study the influence of joints on the failure characteristics of tunnels, three test schemes with different joint lengths, joint spacing, and joint positions are designed. The results show that the bearing capacity of the tunnel decreases with the increase in the joint length. With the increase in joint spacing, the bearing capacity of the tunnel decreases first and then increases. The crack propagation law of the three test schemes has experienced four stages: no crack, crack initiation, crack rapid development, and crack gradual reduction. The location of joints has the greatest influence on the failure mode of the tunnel. The crack is most likely to appear at the top of the tunnel and expand along the joint, mainly because it is easy to form tensile stress at the top of the tunnel and compressive stress concentration at the joint tip. Therefore, when excavating the tunnel in the underground space, the influence of joints on the tunnel should be considered. Analyzing the relationship between the tunnel and joints has important practical guiding significance for the control of the surrounding rock of the tunnel. Finally, the failure results of the indoor physical model and numerical model are compared and analyzed. They are in good agreement, which also reflects the rationality of numerical simulation.